Annealing of focused ion beam damage in gold microcrystals: an in situ Bragg coherent X‐ray diffraction imaging study. (22nd February 2021) - Yang, David; Phillips, Nicholas W.; Song, Kay; Harder, Ross J.; Cha, Wonsuk; Hofmann, Felix
Abstract : An in situ Bragg coherent X‐ray diffraction annealing experiment on focused ion beam damaged gold microcrystals is presented. Abstract : Focused ion beam (FIB) techniques are commonly used to machine, analyse and image materials at the micro‐ and nanoscale. However, FIB modifies the integrity of the sample by creating defects that cause lattice distortions. Methods have been developed to reduce FIB‐induced strain; however, these protocols need to be evaluated for their effectiveness. Here, non‐destructive Bragg coherent X‐ray diffraction imaging is used to study the in situ annealing of FIB‐milled gold microcrystals. Two non‐collinear reflections are simultaneously measured for two different crystals during a single annealing cycle, demonstrating the ability to reliably track the location of multiple Bragg peaks during thermal annealing. The thermal lattice expansion of each crystal is used to calculate the local temperature. This is compared with thermocouple readings, which are shown to be substantially affected by thermal resistance. To evaluate the annealing process, each reflection is analysed by considering facet area evolution, cross‐correlation maps of the displacement field and binarized morphology, and average strain plots. The crystal's strain and morphology evolve with increasing temperature, which is likely to be caused by the diffusion of gallium in gold below ∼280°C and the self‐diffusion of gold above ∼280°C. The majority of FIB‐induced strains are removed by 380–410°C, depending on which reflection is being considered. These observations highlight the importance of measuring multiple reflections to unambiguously interpret material behaviour.